Change in Geotechnical Properties of a Soil Subject to Laboratory Ignition (2018)
Tropical areas are regions subject to warm environments and their soils, especially in areas covered with vegetation, may be exposed to events such as fires. The high temperatures that can be reached in these events cause variations in some of the geotechnical properties of soils, influencing the behavior of the material, and can give rise to erosive processes, which in many cases precede mass movements. The following article describes what happens in a soil that has undergone an ignition process in the laboratory, analyzing the variations in some physical (moisture content, Atterberg limits, specific gravity and granulometry), chemical (pH and cation exchange capacity), mineralogical, structural and mechanical (suction, disintegration and pinhole test) properties; clearly showing that the material becomes more acidic with a higher void ratio, less cation exchange capacity, less kaolinite, plasticity and suction, and variation in texture, with a consequent increase in erodibility.